Temperature resistance coefficient of doped with rare earth elements nanostructured silicon films - A. S. Strogova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2021)
The regularities of changes in the concentration of an electrically active dopant in a nanostructured silicon film by changing the electrical resistivity depending on the doping conditions were investigated. The dependences of the changes in the obtained structures doped with rare-earth elements, such as La, Eu, Sm, Dy, Gd (lanthanides), on nanostructured silicon films are determined. The regularities of the obtained films changes and the temperature coefficient of resistance (TCR) change depending on the formation conditions are established. The regularities of the TCR are shown depending on the selected conditions for doping or non-doping of nanostructured silicon films with various impurities. It is shown that the main conditions under which the effect and change in the temperature coefficient of resistors resistance on thin films using rare-earth elements, such as oxygen, boron and phosphorus in the bulk of the film, is considered to be the temperature effect after deposition.